Maxim Shaligin’s Ballet “Hopper”: at the Crossroads of Interspecific Interpretation and Artistic Translation - Zinchenko, Veronika (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. Maxim Shalygin’s ballet “Hopper” is for the first time explored both from the point of view of its genre and intonation specifics, and in terms of interspecific connections with the painting by American artist Edward Hopper “Morning Sun”. The author’s methods of interspecific literary translation of E. Hopper’s style are revealed by immanently intonation means. The expediency of using the definition of intermedial interpretation, which is a kind of interpretation by composer of a work of a related art form by means of interspecific literary translation, has been substantiated. The relevance of the study is due to the first scientific appeal to the ballet work of the Ukrainian-Dutch composer Maksim Shalygin (1985) in the context of an intermedia composer’s interspecific. An analytical study of M. Shalygin’s ballet "Hopper" with an emphasis on identifying the specifics of the transplantation of E. Hopper’s style into the genre-intonational essence of ballet provides the innovative status of the presented study. The main objective of the study is to reveal the interpretational specifics of M. Shalygin’s ballet “Hopper” in the aspect of intermedial interpretation. Based on the study of the artistic style of E. Hopper (in particular, his painting “Morning Sun”), the features of the composer’s work on the “translation” and transplantation of the artist’s style into the immanent-musical plane (the model of “pictorial music”) are investigated. The following research methods are adapted in the work: the comparative method (to compare the genre features of M. Shalygin’s ballet and E. Hopper’s painting), the method of genre-intonation analysis — to highlight the immanently musical specifics of ballet; the method of theoretical generalization — for understanding the tendencies of the composer’s work in the intermedial space. Results. In the course of the research, it was found that M. Shalygin, who displays a tendency to-wards intermedial artistic thinking in his work, creates in the ballet “Hopper” an interpretation and sound commentary on the painting by E. Hopper. An important feature of the ballet is the process of transformation at all levels of genre-intonation organization. It is a partial rethinking of the themes of his already existing work “Duet” with the transformation of a non-ballet work into a ballet one proper, and, if we take into account the author’s title of the work “Serenade”, a transformation of the serenade`s genre, which in the process of development loses its real genre coordinates, and, occurrence intonational “transformers” from two ballet themes, each of which represents the main features of E. Hopper’s work (clarity of lines, playing with the light’s). In the process of intermedial interpretation, the phenomenon of “musical painting” is born, which realizes the artistic translation of the American artist’s style by means of music. Thanks to finding musical and intonational equivalents to the main stylistic features of the artist (clear geometric lines, playing with light, the imaginative system of loneliness and alienation) M. Shalygin manages to create a picturesque picture by intonation means.